2017
DOI: 10.1371/journal.pone.0182260
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reaction between Formosan termite (Coptotermes formosanus) proteins and cockroach allergens

Abstract: Cockroach allergens can lead to serious allergy and asthma symptoms. Termites are evolutionarily related to cockroaches, cohabitate in human dwellings, and represent an increasing pest problem in the United States. The Formosan subterranean termite (Coptotermes formosanus) is one of the most common species in the southern United States. Several assays were used to determine if C. formosanus termite proteins cross-react with cockroach allergens. Expressed sequence tag and genomic sequencing results were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The genomes of two termites–– C. secundus and Z. nevadensis ––were first published in 2018; however, detailed attention has been paid to their evolutionary relationship, social behavior, and adaptation to the urban environment 25,59 . The comparative genomics in this study not only proved the expansion of multiple gene families in Blattodea species but raised the possibility that termites may contain highly identical allergens that are cross‐reactive with those of cockroach and other arthropods 63 . Despite that, the highly diversified protein sequences in the GST family in cockroach and termites also pointed out the complexity in their molecular surface structures and therefore making low‐identical GSTs, such as Bla g 5, Der p 8, Blo t 8, and Asc s 13, less cross‐reactive among different species 64 …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The genomes of two termites–– C. secundus and Z. nevadensis ––were first published in 2018; however, detailed attention has been paid to their evolutionary relationship, social behavior, and adaptation to the urban environment 25,59 . The comparative genomics in this study not only proved the expansion of multiple gene families in Blattodea species but raised the possibility that termites may contain highly identical allergens that are cross‐reactive with those of cockroach and other arthropods 63 . Despite that, the highly diversified protein sequences in the GST family in cockroach and termites also pointed out the complexity in their molecular surface structures and therefore making low‐identical GSTs, such as Bla g 5, Der p 8, Blo t 8, and Asc s 13, less cross‐reactive among different species 64 …”
Section: Discussionmentioning
confidence: 80%
“…25,59 The comparative genomics in this study not only proved the expansion of multiple gene families in Blattodea species but raised the possibility that termites may contain highly identical allergens that are cross-reactive with those of cockroach and other arthropods. 63 Despite that, the highly diversi- S14). 32,[65][66][67][68][69] The incorporation of the old collective with our newly identified allergens, especially those belonging to novel groups, could potentially result in diagnostic tests with stronger IgE sensitivity and thus improve the efficacy and accuracy of species-specific component-resolved diagnosis in certain populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that TM is an important allergen in other crustaceans, such as crabs (Cha f 1, Por p 1, Scy p 1) and lobsters (Pan s 1, Hom a 1, Pan s 1), as well as mollusks such as oysters (Cra a 1, Cra g 1, Sac g 1), gastropods (Hal l 1, Hal m 1, Hel as 1), and squid (Tod p 1) (Table 3). In addition to shellfish, it is characterized as a food allergen in herring worm (Ani s 3) [78], common roundworm (Asc l 3), silk moth (Bomb m 3) [79], and Mozambique tilapia (Ore m 4) [80], as an airway allergen in mosquitoes (Aed a 10) [81], cockroaches (Bla g 7, Per a 7) [82,83], mites (Blo t 10, Cho a 10, Der f 10, Der p 10, Lep d 10, Tyr p 10) [84][85][86][87][88][89], and termites (Copt f 7) [81], and as an injection allergen in midges (Chi k 10) [90]. AK is also a widely distributed invertebrate pan-allergen with remarkably conserved sequences and shows cross-reactivity with allergens from crab (Cal b 2, Scy p 2) and oyster (Cra a 2) (Table 3).…”
Section: Cross-reactivity Of Shrimp Allergensmentioning
confidence: 99%
“…Several termite proteins, including tropomyosin orthologs of Bla g 3 and Bla g 7, were shown to cross-react with cockroach allergens. 42 The investigators described that the C. formosanus tropomyosin was identical to tropomyosin from American (99% identify with Per a 7) and German (98% identify with Bla g 7) cockroaches. In addition, they demonstrated that a recombinant termite tropomyosin cross-reacted with IgE from patients with cockroach and shrimp allergy.…”
Section: Tropomyosin and Insectsmentioning
confidence: 99%